Shopping for Health: Foods with Added Fiber - Wendy J, Dahl (EDIS)
Fiber in foods consists of carbohydrates that cannot be digested. Although many foods naturally contain fiber, high-fiber ingredients are commonly added to foods to increase their fiber content. Fiber ingredients may be added to foods for health or functional reasons. This 3-page fact sheet was written by Wendy Dahl, and published by the UF Department of Food Science and Human Nutrition, November 2013. http://edis.ifas.ufl.edu/fs235